A metapsicologia freudiana e a topologia lacaniana: formalização e transmissão do saber clínico - Feitosa, Lucas Wagner Brígido (2023)
This master's dissertation consists of a report on the research that was based on the premise that there would be a link that could be established between Freudian metapsychology and Lacanian topology. The methodology adopted to address the problem raised sought to combine the theoretical study of texts chosen based on criteria drawn up in connection with the objective of the research and sought to maintain in inseparable connection the psychoanalytic clinic with its theoretical formalization. More precisely, its direction consisted of scrutinizing the conditions that are supposed to permeate this link, and two of its main effects: the formalization and the transmission of the psychoanalytic clinical knowledge. For this purpose, the link between psychoanalysis, ancient science and modern science, which enabled its emergence, was first examined. Next, the delimitation of the invariants refined from the Freudian topological methodology was carried out, and the way in which they made metapsychological conceptualizations and schematizations possible was demonstrated. From the treatment of these invariants, which are at the basis of metapsychological articulation, a consideration of topology was inferred already in Freud, which refers to the timelessness of the unconscious. This moment of research was also dedicated to resuming points related to Lacan's topological developments through aspects jointly concerned with Freud's topological methodology, namely: language, logic, time-space and sex. Furthermore, the possibilities for the emergence, formalization and transmission of psychoanalysis were under discussion. The elements of the link proposed in the study – metapsychology and topology – presented in common the issue of formalization and the subsequent transmission, which take into account the clinical singularity and prevent it from transmuting into the ineffable mystical or the unspeakable. The third moment of the investigation consisted of examining the clinical dimension of the link between topology and metapsychology, and for this purpose it adopted the symptom as its basic question, highlighting that the analytical logos comes from pathos. It is concluded that Freud distanced himself from the nosology and nosography of his time and that Lacan articulated two ways of thinking about the clinic: structural and Borromean.